Hands-On Penetration Testing on Windows: Unleash Kali Linux, PowerShell, and Windows Debugging Tools for Security Testing and Analysis - Bramwell, Phil (Packt Publishing, Limited, 2018)
Penetration testing is highly competitive, and it's easy to get stuck in the same routine client after client. This book will provide hands-on experience with penetration testing while guiding you through behind-the-scenes action along the way.